Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite

Efficient synthesis of 3,3′-Spirooxindole γ-Butyrolactone via Rongalite-mediated domino reductive aldol and spiro-lactonization reactions - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Kinage, Anil K. (ChemistrySelect, 2025)
In this study, we develop a novel methodology involving rongalite-mediated domino reductive/aldol reaction, followed by spiro-lactonization of 2-oxoindolin-3-ylidene acetates/malonates in presence of base to synthesis of 3,3 `-spirooxindole gamma-butyrolactone. The detail study, such as effect of solvent, effect of different base and substrate has been carried out. Scale up of this methodology is also done. Sodium hydroxymethanesulfinate dihydrate (rongalite) concurrently has a dual role in this context; it acts as a reducing agent as well as C1 synthon. This approach offers several advantages, such as being metal- and catalyst-free, involving a simple reaction protocol, having a wide substrate scope, using water as a green solvent, and providing good to excellent yields of the products under mild reaction conditions.
Keywords: (+/-) Coixspirolactam A & [3; 3 `-spirooxindole gamma-butyrolactone]; Domino reductive/aldol/spiro-lactonization; Good step economy; Rongalite as reductant & C1 synthon; Water as a green solvent

Evaluation of reaction kinetics for chemoselective hydrogenation of citral for intensification of citral intermediates using copper-based catalysts - Debtirtha, Banik; Kinage, Anil K.; Vasireddy, Satyam Naidu (Indian Chemical Engineer, 2025)
Citral intermediates’ formation kinetics is studied using non-noble metal catalyst (Cu/SiO2) to evaluate catalyst performance characteristics via chemoselective hydrogenation of citral. The catalyst is synthesised by the precipitation method and characterised using XRD, FESEM and BET surface area analyser. Hydrogenation experiments are carried out using an Autoclave reactor in the temperature range of 80–120°C, pressure range of 10–50 bar and for catalyst loadings of 0.5, 1 and 1.5 g. The intermediates product distribution comprises aldehyde and alcohol formation such as citronellal, nerol and citronellol formation. The performance of the Cu/SiO2 catalyst is evaluated using the parameters such as citral conversion, citronellol selectivity and yield as 96.96%, 95.30% and 92.30%, respectively under optimal conditions of 50 bar, 120°C and 1 g catalyst for the reaction time of 100 min. The absence of internal and external mass transfer limitations is verified using the Carberry number and Weisz-Prater modulus criterion. The intrinsic kinetics of the gas–liquid phase hydrogenation of citral is determined using the Langmuir–Hinshelwood-Hougen-Watson (LHHW) model for citral intermediates formation. The reaction kinetic parameters show that citronellol formation favours by the nerol route compared to citronellal conversion.